2013
DOI: 10.1080/09585192.2011.616526
|View full text |Cite
|
Sign up to set email alerts
|

The reception of Anglo leadership styles in a transforming society: the case of American companies in Vietnam

Abstract: This article examines the transfer of Anglo leadership styles in a transforming society. It aims to investigate the transferability of two American leadership styles, namely performance-oriented and participative styles, to Vietnamese subsidiaries. Utilising an exploratory case study approach, this article presents evidence of a strong acceptance of these leadership styles, and tries to ascertain whether the adoption of a humane style of leadership in line with Vietnamese traditions is a means of leaders recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…The joint ventures on the other hand were more inclusive and participative. In a more recent study, Vo and Hannif (2013) observed the same. They noted that the local companies may be more autocratic and collective but the multinationals and the joint ventures were decidedly more participative.…”
Section: Vietnamese Work Culturesupporting
confidence: 61%
“…The joint ventures on the other hand were more inclusive and participative. In a more recent study, Vo and Hannif (2013) observed the same. They noted that the local companies may be more autocratic and collective but the multinationals and the joint ventures were decidedly more participative.…”
Section: Vietnamese Work Culturesupporting
confidence: 61%
“…It is expected that, if properly implemented, management initiative practices are likely to make use of the knowledge, skills, abilities, and willingness of employees to activate their creativity (Fu, Flood, Bosak, Morris, & O'Regan, ). Also of note is that organizations are increasingly becoming aware that people management is central to modern administration management practices (see Cabrera & Cabrera, ; A. Vo & Hannif, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Vietnamese firms that wish to pursue innovative HR practices often learn and translate “best practices” into their actual implementation. Finally, Vietnamese organizations now prefer to promote young leaders, who are willing to adopt modern management styles, and thus adopt and implement HRM practices from Western countries (see also A. Vo & Hannif, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show the local employees' increasing openness and expectations for work autonomy and participation (Vo & Hannif 2013 …”
Section: More'mentioning
confidence: 99%